Sufragistas - Streep, Meryl, 1949-; Gavron, Sarah; Speak Up (Barcelona RBA revistas, 2015)
A drama that tracks the story of the foot soldiers of the early feminist movement, women who were forced underground to pursue a dangerous game of cat and mouse with an increasingly brutal State. These women were not primarily from the genteel educated classes, they were working women who had seen peaceful protest achieve nothing. Radicalized and turning to violence as the only route to change, they were willing to lose everything in their fight for equality - their jobs, their homes, their children and their lives. Maud was one such foot soldier. The story of her fight for dignity is as gripping and visceral as any thriller, it is also heart-breaking and inspirational.
Acompaña a la revista n. 370
Carey Mulligan, Anne-Marie Duff, Helena Bonham Carter
No recomendada a menores de 7 años
Idiomas : Inglés y castellano. Subt.: inglés (subtítulos speak up) y castellano
Keywords: Películas cinematográficas -- DVD